PENGARUH HARGA DAN PROMOSI TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING DENGAN MODERASI KUALITAS PELAYANAN PADA TOKO MARKAS BELI DI SHOPEE - Abaitunnisa, Fatima; Fandiyanto, Randika; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
In the development of the digital industrial era, people are now starting to recognize online platforms such as e-commerce and marketplaces, which are the shopping platforms of first choice for people in Indonesia to meet their various needs and requirements. The aim of this research is to analyze and test the influence of price and promotion on consumer satisfaction through purchasing decisions with service quality as moderation. This research is explanatory research. The population in this study was buyers of the Markas Beli store. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this research used the Partial Least Square Structural Equation Model (PLS-SEM). Hypothesis test results of direct influence using the Smart PLS 3.0 application, Price has a significant positive effect on purchasing decisions, Promotion has a significant positive effect on purchasing decisions, Price has a positive but not significant effect on consumer satisfaction, Promotion has a positive but not significant effect on consumer satisfaction, Purchasing decisions have an effect significant positive effect on consumer satisfaction, service quality has a positive but not significant effect in moderating price on consumer satisfaction. The results of the indirect effect hypothesis test show that the price variable has a significant positive effect on consumer satisfaction through purchasing decisions. Price has a significant positive effect on consumer satisfaction through purchasing decisions.